The CXCL8-CXCR1/2 Axis as a Therapeutic Target in Breast Cancer Stem-Like Cells - Ruffini, Pier Adelchi (Frontiers in Oncology, 2019)
Cancer Stem Cells have been targeted by different strategies over the last decade. This review focuses on preclinical and clinical results obtained by interfering with chemokine receptors CXCR1 and CXCR2, particularly in breast cancer